Authority of Traditional Villages in Cultural Tourism Management in Bali (A Case Study of Mertasari Beach Management in South Denpasar District) - I Putu Yudi Sumertana; Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The management of tourism closely tied to Balinese culture emphasizes the significant role of traditional villages, including Desa Adat Intaran, which is responsible for managing Mertasari Beach in South Denpasar District. This research aims to examine: (1) the authority of traditional villages in managing cultural tourism in Bali based on Regional Regulation Number 4 of 2019 concerning Traditional Villages; and (2) the contribution of Desa Adat Intaran in the management of Mertasari Beach. This research uses a qualitative approach with interactive data analysis techniques adapted from Miles and Huberman. The research findings indicate that: (1) Based on the Bali Provincial Regional Regulation Number 4 of 2019 concerning Traditional Villages, traditional villages have the authority to manage tourism that is part of the traditional village's heritage, especially if it is related to Padruwen Desa. This Regional Regulation strengthens the role of traditional villages in managing Balinese cultural tourism by considering the local values of the Balinese community, particularly in preserving Padruwen Desa as a tourist destination; and (2) Although Desa Adat Intaran has been active in managing Mertasari Beach, including community empowerment programs, environmental conservation, cleanliness of Mertasari Beach, and financial planning, the management structure separate from the traditional village organization is still not optimal. Community participation and supervision include overseeing the workforce, security, and vendor activities.